Hubungan Kondisi Fisik Dengan Hasil Prestasi Kelas Tanding Atlet Pencak Silat - Fikry, Azmal; Wahyudi, Usman (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
The last two matches attended by athletes from the Segorogeni pencak silat school found that athletes in the same sparring category achieved different performances, raising suspicions that different physical conditions could affect athletes' performance achievements. The aim of this research is to determine the relationship between physical condition and performance in athletes from the Segorogeni pencak silat school. Subjets in this study includes all 37 active members, consisting of 22 males and 15 females. Data collection was carried out using test and non-test instruments. Non-test instruments included interviews and observations, while test instruments involved a series of tests to determine strength, balance, explosive power, speed, and endurance levels. Hypothesis testing using the Spearman rank correlation test yielded a significance value <0.05, with a significance value of 0.046 for both variables and a correlation strength level between physical condition and performance at 0.329, indicating a moderate correlation. These results indicate that the physical condition of athletes from the Segorogeni pencak silat school is related to their performance in sparring classes.